2020
DOI: 10.1007/s00248-020-01585-8
|View full text |Cite
|
Sign up to set email alerts
|

Diffusible Signaling Factor, a Quorum-Sensing Molecule, Interferes with and Is Toxic Towards Bdellovibrio bacteriovorus 109J

Abstract: Bdellovibrio bacteriovorus 109J is a predatory bacterium which lives by predating on other Gram-negative bacteria to obtain the nutrients it needs for replication and survival. Here, we evaluated the effects two classes of bacterial signaling molecules (acyl homoserine lactones (AHLs) and diffusible signaling factor (DSF)) have on B. bacteriovorus 109J behavior and viability. While AHLs had a non-significant impact on predation rates, DSF considerably delayed predation and bdelloplast lysis. Subsequent experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Because of the special lifestyle of Bdellovibrionota, there may be other protein factors serving as the quorum sensing regulators during the predatory growth phase. The latest study indicated that diffusible signaling factor (DSF) considerably delayed predation and bdelloplast lysis (40). Sec-type II system is almost complete in all Bdellovibrionota groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the special lifestyle of Bdellovibrionota, there may be other protein factors serving as the quorum sensing regulators during the predatory growth phase. The latest study indicated that diffusible signaling factor (DSF) considerably delayed predation and bdelloplast lysis (40). Sec-type II system is almost complete in all Bdellovibrionota groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DSF has multiple effects on various cellular processes of bacteria. It has been reported that DSF can block protease secretion from attack-phase cells of Bdellovibrio bacteriovorus 109 J completely at the concentration of 50 mM and negatively regulate the membrane integrity at a concentration of 200 mM [75]. Additionally, DSF inhibits biofilm formation with no impacts on the growth of P. aeruginosa under static and continuous conditions [76].…”
Section: Discussionmentioning
confidence: 99%
“…At 50 μM, XcDSF reduced strain 109J attack-phase motility by 50%. A higher dose of 200 μM leads to a significant loss in membrane integrity and the viability of strain 109J [58]. Transcriptome analysis revealed that XcDSF induced stress responses, including osmotic shock, reactive oxygen species (ROS), MarR regulon activation, and the downregulation of the flagellum assembly genes and serine protease genes in 109J [58].…”
Section: Communication Between B Cenocepacia and Francisella Novicidamentioning
confidence: 99%
“…A higher dose of 200 μM leads to a significant loss in membrane integrity and the viability of strain 109J [58]. Transcriptome analysis revealed that XcDSF induced stress responses, including osmotic shock, reactive oxygen species (ROS), MarR regulon activation, and the downregulation of the flagellum assembly genes and serine protease genes in 109J [58]. Furthermore, XcDSF at a concentration of 200 μM was shown to have similar inhibitory activity towards B. bacteriovorus as sodium dodecyl sulfate, a highly toxic chemical surfactant, whereas it only altered gene expression of this predator at a lower and nontoxic concentration of 50 μM [58].…”
Section: Communication Between B Cenocepacia and Francisella Novicidamentioning
confidence: 99%